2021
DOI: 10.1136/bmj.n826
|View full text |Cite
|
Sign up to set email alerts
|

Linked electronic health records for research on a nationwide cohort of more than 54 million people in England: data resource

Abstract: Objective To describe a novel England-wide electronic health record (EHR) resource enabling whole population research on covid-19 and cardiovascular disease while ensuring data security and privacy and maintaining public trust. Design Data resource comprising linked person level records from national healthcare settings for the English population, accessible within NHS Digital’s new trusted research environment. Setting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 15 publications
3
125
0
2
Order By: Relevance
“…Among the 149 eligible articles, 227,351,954 participants were included in our meta-analysis; and 89,235,737 were COVID-19 patients. We included 27 studies (132,727,798 participants) for susceptibility [ [20] , [21] , [22] , [23] , [24] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] , 132 , 166 ], 56 studies (83,097,968 participants) for illness severity [ 21 , 24 , 28 , 31 , 32 , 34 , [38] , [39] , [40] , [41] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , 83 , 108 , 110 , 116 , 117 ...…”
Section: Resultsmentioning
confidence: 99%
“…Among the 149 eligible articles, 227,351,954 participants were included in our meta-analysis; and 89,235,737 were COVID-19 patients. We included 27 studies (132,727,798 participants) for susceptibility [ [20] , [21] , [22] , [23] , [24] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] , 132 , 166 ], 56 studies (83,097,968 participants) for illness severity [ 21 , 24 , 28 , 31 , 32 , 34 , [38] , [39] , [40] , [41] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , 83 , 108 , 110 , 116 , 117 ...…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that missing data within clinical records can provide unbiased estimates of adjusted exposure-outcome associations under a wide range of missing data assumptions [25]. In addition, primary care data in England provide some of the most detailed electronic health-care records internationally and are routinely used to identify individuals at risk of chronic and infectious diseases, including COVID-19 mortality [19,26], giving this study real world utility. This study utilized data from the 2011 Census, therefore any sociodemographic changes within the last decade will not be reflected in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cohort analysis using the newly established NHS Digital Trusted Research Environment (TRE) for England which provides secure, remote access to linked, person level EHR data for over 56 million people[12]. Available data sources cover primary care, secondary care, pharmacy dispensing, death registrations and COVID-19 tests and vaccines.…”
Section: Methodsmentioning
confidence: 99%
“…This study, therefore, set out to conduct the largest scale evaluation of AT use in individuals with AF to date in routinely updated, linked, population-scale electronic health record (EHR) data for 56 million people in England[12]. Utilising this statistical power, this study investigated what factors are associated with pre-existing AT use and whether pre-existing AT use (across sub-types) may reduce COVID-19 related hospitalisation and death.…”
Section: Introductionmentioning
confidence: 99%